AKSES MENDAPATKAN KEADILAN (ACCESS TO JUSTICE): HAK KONSUMEN ATAS ALTERNATIF PENYELESAIAN SENGKETA DI LUAR PENGADIALN - Ai Permanasari (Faculty of Law, Maranatha Christian University, 2019)
Access to justice is a mechanism for every person, whose rights are violated, including consumers who are in dispute, to find effective solutions provided by the justice system. The mechanism shouldt be accessible, affordable and easy to understand. This mechanism must be able to provide justice fairly, speedy and without discrimination, and must also provide an alternative dispute resolution. In the case of consumer alternative dispute resolution outside the court, it should provide a great benefit to the community, because the avaibility of the choice to access justice in a way that can be adapted to their needs and abilities. But what is the meaning of the alternative or choice if in the end it cannot be implemented or cannot be executed to what has become decision or agreement of the alternative institution. This is related to the contradiction of the strength of BPSK decisions, in order there are still legal remedies against the BPSK decision, and the execution of the BPSK verdict still relies on the existence of 'fiat' executions from the court. Therefore to ensure access to justice for the consumers, harmonization between courts and consumer alternative disputes resolution system is unavoidable.